PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 43 PADANG - Sari, Vivi Noprita (Jurnal Edukasi dan Penelitian Matematika, 2023)
Achievements/objectives of mathematics subjects include mastery of understanding mathematical concepts that students need to have. In fact, the ability of class IX students of SMPN 43 Padang in this regard is still relatively low. The cause of this is learning that is still focused on educators. To overcome this, the TAI type cooperative model in learning can be used as a solution. Quasi-experimental is a type of research that uses a Randomized Control Group Posttest Only Design. Meanwhile, 87 students in class IX SMPN 43 Padang make up the population. In selecting sample, the researcher used a simple random sampling method. Class IX.1 was chosen as the experimental class and class IX.3 was chosen as the control class. Based on the hypothesis test with a significant level of ? = 0.05 and obtain a P-value = 0.000. This can be interpreted as a P-value < ? = 0.05 causes to be rejected. This research concludes that the ability to understand mathematical concepts of students who study with the TAI cooperative learning model is better than students who learn with the conventional learning model in class IX SMPN 43 Padang.Keywords – The cooperative learning model, team assisted individualization, Ability to Understand Mathematical Concepts.